The Effect of Web-Based Puzzle Media on Enhancing Arabic Reading Comprehension Among Students at Madrasah Tsanawiyah - Rusman, Maman; Fahra, Nurul Azizah; Syamsu, Pradi Khusufi (Nurul Jadid University, 2025)
Improving students’ reading comprehension in Arabic is essential for supporting religious literacy and academic success in Islamic educational contexts. This study investigates the effectiveness of web-based puzzle media in enhancing the Arabic reading comprehension of eighth-grade students at MTs Nurul Ikhsan Cirebon. Employing a quantitative experimental approach with a one-group pretest-posttest design, the research examines how digital puzzle-based activities can foster learner engagement and comprehension. The media was implemented through interactive web tools that required students to reconstruct text content using images and sentences derived from learning materials. Statistical analysis using the paired sample t-test revealed a significant improvement in student performance, with a t-value of 14.9 exceeding the critical t-table value of 2.084 at the 0.05 significance level. The mean score increased from 43.84 (pretest) to 79.17 (posttest), indicating a gain of 35.33 points. These results demonstrate that web-based puzzle media can serve as an effective, engaging, and pedagogically sound tool for improving Arabic reading comprehension in the digital learning era.